Bonding performance of melamine-urea-formaldehyde and phenol-resorcinol-formaldehyde adhesives in interior grade glulam. Issue 23 (2nd December 2017) - Zhou, Jun; Yue, Kong; Lu, Weidong; Chen, Zhangjing; Cheng, Xiucai; Liu, Weiqing; Jia, Chong; Tang, Lijuan
Abstract: Wood moisture content (MC) affects the glued laminated beam (glulam) bonding strength. Selected adhesives were Phenol-Resorcinol-Formaldehyde (PRF) and Melamine-Urea-Formaldehyde (MUF) adhesives with 1, 1.5 and 2% (w/w) carboxymethyl cellulose (CMC) formic acid solutions. Douglas fir (pseudotsuga menziesii) from North America was used in the test. The bonding behavior of these adhesives with wood at 12 and 18% MC were investigated. The study focused on the effect of 18% MC on shear strength performance of MUF and PRF adhesives and optimizing the formula of CMC formic acid solution. Compressive shear strength of wood with MUF adhesive with 2% (w/w) formic acid solution at 12 and 18% MC stabilized at 10.6 and 10.0 MPa, respectively, which were 17 and 16% higher than that with PRF adhesive at the same condition. At 12–18% MC, MC had a little effect on bonding strength. However, 18% MC wood with PRF adhesive had 52.2% less initial strength increasing rate than that of 12% MC wood. 18% MC wood with MUF adhesives with 1, 1.5 and 2% (w/w) CMC formic acid solutions had 16.0, 15.5 and 27.0% less initial strength increasing rates than that of 12% MC wood, respectively. MUF adhesive using 2% CMC formic solution required the shortest press time at 12 and 18% MC about 1.6 and 2.7 h, respectively. The strength of PRF adhesive was significantly affected by wood MC and enough press time is essential for the proper bonding strength.